2014
DOI: 10.1371/journal.pone.0113536
|View full text |Cite
|
Sign up to set email alerts
|

When Do Natural Language Metaphors Influence Reasoning? A Follow-Up Study to Thibodeau and Boroditsky (2013)

Abstract: In this article, we offer a critical view of Thibodeau and Boroditsky who report an effect of metaphorical framing on readers' preference for political measures after exposure to a short text on the increase of crime in a fictitious town: when crime was metaphorically presented as a beast, readers became more enforcement-oriented than when crime was metaphorically framed as a virus. We argue that the design of the study has left room for alternative explanations. We report four experiments comprising a follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
80
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(106 citation statements)
references
References 36 publications
3
80
0
1
Order By: Relevance
“…Contradicting results were also reported across studies. Consider studies conducted by two groups of scholars who examined the effect of two metaphorical frames, namely crime is beast and crime is a virus, on policy preferences (REA: Steen, Reijnierse, & Burgers, 2014;Thibodeau & Boroditsky, 2011. First, Boroditsky (2011, 2013) reported that the crime is a beast frame made people prefer enforcement strategies to reform strategies.…”
Section: Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Contradicting results were also reported across studies. Consider studies conducted by two groups of scholars who examined the effect of two metaphorical frames, namely crime is beast and crime is a virus, on policy preferences (REA: Steen, Reijnierse, & Burgers, 2014;Thibodeau & Boroditsky, 2011. First, Boroditsky (2011, 2013) reported that the crime is a beast frame made people prefer enforcement strategies to reform strategies.…”
Section: Differencesmentioning
confidence: 99%
“…4-7, 2013REA). Consequently, Steen et al (2014), conducted a series of follow-up experiments, in which they compared the effects of the same metaphorical frames to a non-metaphorical control frame. They found no framing effects (Steen et al, 2014, pp.…”
Section: Differencesmentioning
confidence: 99%
“…Ng and Koller, 2013). It is true that addressees do not always verbally pick up on such intentions of deliberate metaphor use --but often they do, in face-to-face interaction (e.g., Tay, 2013) and in media use (e.g., Musolff, 2004;cf. Steen, 2013).…”
mentioning
confidence: 99%
“…Yet, a recent extended replication by Steen et al (2014) did not come to the same conclusions. The authors show that the impact might be due to simple exposure to textual information, rather than metaphors per se.…”
Section: Julien Perrez and Min Reuchampsmentioning
confidence: 87%
“…In their article, linguists W. Gudrun Reijnierse, Tina Krennmayr, Gerard J. Steen and communication scientist Christian Burgers explore "How viruses and beasts affect our opinions (or not): The role of extendedness in metaphorical framing". Following on the on-going debate between Boroditsky's studies (2011, 2013) and their own work (Steen et al, 2014) and the existence of contrasting findings, they investigate whether extending the metaphorical frame of the 'Crime is a virus' metaphor, on the one hand, and of the 'Crime is a beast' on the other, leads to a differentiated impact on the perceived effectiveness of policy measures related to crime solving. More specifically, they analysed to what extent these respective extended metaphorical frames led the subjects to choose either reform-oriented policies (hypothesised as being in line with the former) or enforcement-oriented ones (hypothesised as being in line with the latter).…”
Section: Julien Perrez and Min Reuchampsmentioning
confidence: 99%